Cohort by Education Interactions in Longitudinal Changes in Functional Abilities. (March 2020) - Finkel, Deborah; Ernsth Bravell, Marie
Objective: Investigations of cohort differences in relationships between education and health tend to focus on mortality or self-reported health. We report one of the first analyses of cohort differences in relationships between education and objective measures of functional abilities across the lifespan.Method: Up to 26 years of follow-up data were available from 859 adults from the Swedish Adoption/Twin Study of Aging. The sample was divided into two cohorts by birth year: 1900-1924 and 1925-1948. Latent growth curve models (LGCM) were compared across cohort and educational levels.Results: LGCM indicated divergence between adults with lower and higher educational attainment in longitudinal trajectories of change with age in the Balance and Flexibility factors for the later born cohort only.Discussion: Results support the cumulative advantage theory and suggest that education–health disparities are increasing in recent cohorts, even in counties with national health care systems and strong support of education.